Workshop on Making MPASI as an Effort to Prevent Stunting in Sukoraharjo Village, Kedamean District, Gresik Regency - Budhi Setianto; Siti Nur Hasina; Difran Nobel Bistara; Agus Aan Adriansyah; Edza Aria Wikurendra; Akas Yekti Pulih Asih; Abdul Hakim Fasya; Dwi Handayani (UNUSA Press, 2024)
Stunting is a condition in which a child's body fails to grow due to chronic malnutrition so that the child's age is too short. The prevalence of stunting in children under five according to the World Health Organization (WHO) is the country with the third highest prevalence in the Southeast Asia/South-East Asia Regional (SEAR) region, the prevalence of stunting in Indonesia in children under five in 2017 was 36.4% and in 2018 it was 30.8%. One of the stunting preventions can be provided by providing complementary foods from 6-24 months. By holding a workshop related to making complementary foods to prevent stunting, this workshop aims to provide insight to Sidoraharjo residents about the importance of knowledge in compiling complementary foods, and how to make them, as well as preparing the complementary food process. 87.8% and 16.2% increase in knowledge.